Sanitation Sanitasi Lingkungan dan Tingkat Asupan Protein Hewani Terhadap Kejadian Stunting Pada Balita di Desa Pucak Kabupaten Maros - Ayu Puspitasari; Nurhikmawati Abdullah; Hardianti Alimuddin (An Idea Health Journal, 2024)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, especially in the first 1,000 days of life. Editing is one of the nutritional problems in children globally. Nutrition, sanitation and environmental problems trigger the stunting problem in Indonesia. The type of research carried out was observational analytical research using a cross-sectional study approach. Research location in Pucak Village in January 2024. The population and sample were 59 mothers and toddlers using the total sampling method. The research results obtained were that there was a relationship between clean water quality and the incidence of stunting (p=0.001). There is no relationship between latrine ownership and the incidence of stunting (p=0.421). There is a relationship between ownership of a sewerage channel and the incidence of stunting (p=0.003). There is a relationship between ownership of a trash can and the incidence of stunting (p=0.000). There is a relationship between animal protein intake and the incidence of stunting (p=0.007). There is a relationship between Clean Water Quality, Ownership of Waste Water Disposal Channels, Ownership of Trash Cans, Animal Protein Intake and the incidence of stunting in toddlers in Pucak Village, Tompobulu District, Maros Regency